2015
DOI: 10.1038/ncomms7380
|View full text |Cite
|
Sign up to set email alerts
|

Epsin is required for Dishevelled stability and Wnt signalling activation in colon cancer development

Abstract: Uncontrolled canonical Wnt signaling supports colon epithelial tumor expansion and malignant transformation. Understanding the regulatory mechanisms involved is crucial for elucidating the pathogenesis of and will provide new therapeutic targets for colon cancer. Epsins are ubiquitin-binding adaptor proteins upregulated in several human cancers; however, epsins’ involvement in colon cancer is unknown. Here we show that loss of intestinal epithelial epsins protects against colon cancer by significantly reducing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 69 publications
1
36
0
Order By: Relevance
“…We used site-directed mutagenesis to create expression constructs with mutated versions of VEGFR2, and expressed these or wild-VEGFR2 in HUVEC cells as indicated (Figure 1D). Cells were subsequently stimulated with VEGF to induce VEGFR2 activation and ubiquitination, and processed for immunoprecipitation using epsin 1-specific antibody as previously described (Figure 1D) 9, 33 . We found that WT VEGFR2 co-immunoprecipitated with epsin1; however all of the VEGFR2 mutants impeded binding to epsin1 (Figure 1D).…”
Section: Resultsmentioning
confidence: 99%
“…We used site-directed mutagenesis to create expression constructs with mutated versions of VEGFR2, and expressed these or wild-VEGFR2 in HUVEC cells as indicated (Figure 1D). Cells were subsequently stimulated with VEGF to induce VEGFR2 activation and ubiquitination, and processed for immunoprecipitation using epsin 1-specific antibody as previously described (Figure 1D) 9, 33 . We found that WT VEGFR2 co-immunoprecipitated with epsin1; however all of the VEGFR2 mutants impeded binding to epsin1 (Figure 1D).…”
Section: Resultsmentioning
confidence: 99%
“…Strikingly, there are huge amounts of Dsh protein and RNA deposited in the egg during Drosophila oogenesis by the mother (Perrimon, Engstrom, & Mahowald, 1989; Perrimon & Mahowald, 1987) and hence the zygotic null dsh mutants, originating from a dsh +/− mother, survive and look largely normal all the way to third instar larval stages and some even beyond that. This suggests that either the Dsh protein is very stable which has not been addressed thoroughly yet, but seems unlikely as several ubiquitin-linked enzymes and associated proteasome degradation have been lined to Dsh regulation (for example, Chang et al, 2015; de Groot et al, 2014; Madrzak et al, 2015; Strutt, Searle, Thomas-Macarthur, Brookfield, & Strutt, 2013), or that the dsh RNA is particularly stable and maintained throughout embryogenesis to later developmental stages. As such, only maternal-zygotic double mutant dsh − embryos display the classical Wg/Wnt-signaling canonical defects comparable to wg itself or arm /β-catenin (Perrimon et al, 1989; Perrimon & Mahowald, 1987).…”
Section: Cellular Levels Of Dsh and Redundancy In The Mouse Modelmentioning
confidence: 99%
“…Epsins are reportedly overexpressed in several types of cancer, such as prostate, colon, breast, lung, and skin cancers [49]. A recent study using a genetic mouse model reveals that loss of intestinal epithelial epsins protect against colon cancer by significantly reducing the stability of the crucial Wnt signaling effector, dishevelled, and impairing Wnt signaling [50]. Further studies are needed to delineate the intrinsic roles of epsins.…”
Section: Perspectivesmentioning
confidence: 99%